Tabletting forming method of Cr-based catalyst

The Cr-based catalyst powder was prepared by co-precipitation method, and combined with the use of additives, the powder properties and molding properties of the catalyst were optimized, and the problems of small compression ratio and low fault tolerance during the tableting molding process were solved, thus achieving the problem of low compression ratio and low fault tolerance of the Cr-based catalyst in the molding process. The stability and efficient molding of the catalyst molded body are achieved.

CN119386935AActive Publication Date: 2025-02-07CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310920459.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-07
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

During the tablet forming process, the Cr-based catalyst has high brittleness and small compression ratio, which leads to excessive height of the molded body and low fault tolerance of the tableting process, making it difficult to meet the industrial application index.

Method used

The Cr-based catalyst powder is prepared by co-precipitation method, and then mixed with additive I (such as cellulose) and dried, crushed, and sieved, followed by mixing with additive II (such as graphite) and additive III (such as starch). Tablet and secondary calcination are carried out to optimize the powder properties and molding properties of the catalyst.

Benefits of technology

The compression ratio of the Cr-based catalyst and the fault tolerance of the tableting process are improved, ensuring that the radial strength, height and surface area index of the molded body meet the application requirements, and the physical and chemical properties of the catalyst are stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004358507230000151
    Figure BDA0004358507230000151
Patent Text Reader

Abstract

The invention discloses a tabletting forming method of a Cr-based catalyst. The method comprises the following steps: (1) preparing Cr-based catalyst powder by adopting a coprecipitation method; the Cr-based catalyst powder is roasted powder; (2) mixing the Cr-based catalyst powder obtained in the step (1), an aqueous solution of an auxiliary agent I and selectively added water to obtain a mixed material; (3) drying, crushing and screening the mixed material obtained in the step (2), mixing with an auxiliary agent II and an auxiliary agent III, and tabletting to obtain tablets; and (4) roasting the tablets prepared in the step (3) to obtain the formed catalyst. The Cr-based catalyst prepared by the method does not have the problems of layering, transverse cracking, uncapping and the like, and has stable physical and chemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a tabletting method for a Cr-based catalyst, belonging to the technical field of catalyst preparation. Background Art

[0002] Tablet molding is a process of changing the density and strength of catalyst powder particles by applying pressure to achieve catalyst molding. Compared with other catalyst molding methods, tablet molding has the following advantages: the particle size of the molded product is consistent and the quality is uniform; a product with a high bulk density and good catalyst strength can be obtained; the catalyst surface is smooth. Therefore, the tablet molding method has a wide range of industrial application value. The tableting process is divided into six processes: filling and feeding, powder thickening, compaction, deformation (elastic deformation, plastic deformation), particle rupture and pressure rebound. In these processes, the properties of the powder have a crucial influence on compression molding.

[0003] As a material with high density and high brittleness, Cr-based catalysts have weak compression ability and small deformation degree. This property leads to many difficulties in the preparation process of industrial catalysts. First, the high brittleness leads to a small powder compression ratio, which results in a high dead point position of the upper punch under the same pressure conditions (i.e., the position where the pressure limit is reached), resulting in the height of the molded body being too high and failing to meet the height index requirements; if the height of the molded body meets the index requirements, it is necessary to further increase the pressure given by the machine, which will cause the particles to begin to break under excessive stress. In addition, during the tableting process, the compression ratio of the powder is small. When the pressure given by the machine is withdrawn, the tablets are very likely to produce tiny elastic expansions, causing the molded objects to break. These phenomena lead to a narrow adjustable range of tablet press parameters and a low fault tolerance rate in the tableting process during the molding process of Cr-based catalysts. Therefore, it is urgent to seek a method to optimize the properties of Cr-based catalyst powders and improve the fault tolerance of the tableting process.

[0004] CN109569742A discloses a method for improving the tableting strength of silicon-based catalysts. The method comprises: (a) granulating the catalyst to obtain catalyst particles of 1 to 6 mm; (b) crushing and screening the catalyst particles obtained in step (a) to obtain catalyst particles of 10 to 60 mesh; (c) mixing the catalyst particles obtained in step (b) with catalyst powder having a particle size of less than 60 mesh, and then tableting to obtain a catalyst. The method is suitable for tableting of silicon-based catalysts, but the properties of Cr-based catalysts are different from those of silicon-based catalysts. For tableting of Cr-based catalysts, this method is not applicable. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a tableting method for a Cr-based catalyst. The method can effectively improve the compression ratio of the feed material and the fault tolerance of the tableting process. The prepared Cr-based catalyst has no problems such as delamination, transverse cracking, and cap removal, and has stable physical and chemical properties. The radial strength, height, specific surface area, average pore size, and pore volume of the catalyst molding body all meet the application indicators and can be applied to ester hydrogenation or alcohol dehydrogenation reactions.

[0006] The present invention provides a tableting method for a Cr-based catalyst, comprising:

[0007] (1) preparing Cr-based catalyst powder by co-precipitation method; the Cr-based catalyst powder is calcined powder;

[0008] (2) mixing the Cr-based catalyst powder obtained in step (1), the aqueous solution of the additive I and the optionally added water to obtain a mixed material;

[0009] (3) drying, crushing, and screening the mixed material obtained in step (2), and then mixing with auxiliary agent II and auxiliary agent III, and tableting to obtain tablets;

[0010] (4) calcining the tablets prepared in step (3) to obtain the molded catalyst.

[0011] Furthermore, in the Cr-based catalyst powder obtained in step (1), the mass fraction of Cr is 40wt% to 100wt%. Preferably, the Cr-based catalyst powder may also include a metal additive, which is selected from at least one of Cu and Fe. The metal additive accounts for 0wt% to 60wt% of the mass of the Cr-based catalyst powder.

[0012] Furthermore, the coprecipitation method described in step (1) can be carried out by conventional methods, for example: adding a metal salt solution and an alkali solution to a reactor in parallel or in a forward or reverse manner, reacting at 30°C to 90°C for 1h to 2h, maintaining the reaction pH at 6.0 to 9.0, placing the reaction at 25°C to 90°C for aging for 2h to 12h, filtering, washing, and drying the slurry to prepare a catalyst precursor. The metal salt solution is an acidic solution, Cr is present in the form of chromic anhydride and / or chromium nitrate, and other metal additives are present in the form of at least one of nitrates, sulfates, or chlorides. The alkali solution is at least one of ammonia water, ammonium carbonate solution, ammonium bicarbonate solution, sodium carbonate solution, sodium bicarbonate solution, and sodium hydroxide solution.

[0013] Furthermore, the Cr-based catalyst powder in step (1) is a calcined powder, and the calcination conditions are as follows: the calcination temperature is 350°C to 650°C, the calcination time is 3h to 6h, and the calcination atmosphere is an oxygen-containing atmosphere, such as air.

[0014] Furthermore, in step (2), the auxiliary agent I is cellulose; preferably at least one selected from carboxymethyl cellulose and hydroxypropyl methyl cellulose; further preferably, the viscosity of the carboxymethyl cellulose is 200mpa.s to 1000mpa.s, and the viscosity of the hydroxypropyl methyl cellulose is 2000mpa.s to 6500mpa.s. The mass content of cellulose in the aqueous solution of the auxiliary agent I is 1wt% to 10wt%.

[0015] Furthermore, in step (2), the amount of the additive I added is 1 wt% to 3 wt% of the Cr-based catalyst powder.

[0016] Furthermore, in step (2), the amount of water added is such that the final water content of the prepared mixed material is 50wt% to 80wt%.

[0017] Furthermore, in step (3), the drying temperature is 80° C. to 120° C., and the moisture content of the material after drying is 2wt% to 10wt%.

[0018] Furthermore, in step (3), the crushing method can be swing granulation and / or mechanical ball milling.

[0019] Furthermore, in step (3), the screening is divided into three parts according to ≥40 mesh and <80 mesh, 80 mesh to 120 mesh and >120 mesh, and the three parts of materials are mixed in a mass ratio of 10-20:60-80:5-10.

[0020] Furthermore, in step (3), the auxiliary agent II is graphite, and the graphite is at least one of natural graphite and artificial graphite. The natural graphite is flake graphite. The particle size of the auxiliary agent II is above 200 mesh, preferably 400 mesh to 2000 mesh.

[0021] Furthermore, in step (3), the amount of additive II added is 0.5wt% to 3wt% of the Cr-based catalyst powder.

[0022] Furthermore, in step (3), the auxiliary agent III is at least one of starch, epoxy resin, carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol, sesbania powder, and stearic acid.

[0023] Furthermore, in step (3), the amount of additive III added is 1 wt% to 5 wt% of the Cr-based catalyst powder.

[0024] Furthermore, in step (4), the calcination temperature is 300°C to 600°C, the heating rate is 0.5°C / min to 5°C / min, and the calcination time is 2h to 8h.

[0025] Furthermore, the shaped catalyst is preferably cylindrical, with a diameter of 3.0 mm to 5.0 mm and a height of 2.5 mm to 6.0 mm. For example, the commonly used specifications in industry are 3 mm×2.5 mm to 3 mm×3.5 mm or 5 mm×4 mm to 5 mm×6 mm.

[0026] The second aspect of the present invention provides a Cr-based catalyst obtained by the above preparation method.

[0027] Furthermore, the radial strength of the Cr-based catalyst is 50 N / grain or more, preferably 60 N / grain to 120 N / grain, and the specific surface area is 20 m 2 / g~50m 2 / g, average pore diameter is 15nm~35nm, pore volume is 0.08cm 3 / g~0.15cm 3 / g.

[0028] Furthermore, the application field of the catalyst is ester hydrogenation or alcohol dehydrogenation.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The Cr-based catalyst powder is first mixed with the auxiliary agent I. One of the functions is to help the catalyst powder to form agglomerates and have a certain strength to obtain a pre-densified material. The hardness of the pre-densified material is much greater than that of the catalyst powder, so after being subjected to the pressure of the punch, the material in the mold is more easily compressed. Pre-densification can optimize the mechanical properties of the material and make the molded body more deformable. The second function is that the interaction between the auxiliary agent I and the powder particles produces crystallization, bonding and surface tension, which can increase the plasticity of the powder particles and optimize the compression performance of the catalyst powder. Combined with the screening process, large particles and small particles can be closely stacked in the filling link, thereby ensuring that the filling efficiency is maintained in the filling and feeding link. Through the synergistic effect of steps (2) and (3), the powder compression performance can be optimized to the greatest extent, and the height of the finished tablet can be further reduced under the premise of meeting the tablet strength index and the particle stacking ratio index requirements, and the reduction space can reach 9%.

[0031] (2) During the secondary calcination of the catalyst, additives I and III are partially pyrolyzed, and the pyrolyzed components are mostly volatilized in the form of gas, thereby achieving pore formation. The average pore size of the formed catalyst is increased, further improving the internal diffusion rate of reactants and products in the catalyst during the reaction.

[0032] (3) During the process of treating, tableting and calcining the catalyst powder, the introduced components may be pyrolyzed and volatilized during the secondary calcination process, or may be chemically inert. Therefore, the method of the present invention can achieve stable molding of the catalyst and maintain the reaction activity of the catalyst without changing the catalyst composition.

[0033] (4) The present invention performs comprehensive treatment on the Cr-based catalyst powder to obtain a material with optimized compression performance and increased compression ratio for tableting, which can effectively improve the adjustability of the tableting process and contribute to the stable operation of the tableting process. DETAILED DESCRIPTION

[0034] The present application is described in detail below in conjunction with the examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials in the examples of the present invention are purchased through commercial channels. In the examples, unless otherwise specified, the technical means used are the technical means conventional in the art.

[0035] In the present invention, the strength is measured by using a ZQJ-Ⅲ intelligent particle strength testing machine, and the average radial strength value is obtained by multiple measurements.

[0036] In the present invention, the height of the catalyst molding is measured using a vernier caliper, and the average height value is obtained by multiple measurements.

[0037] In the present invention, the specific surface area, average pore size and pore volume of the catalyst are analyzed by using a N2 physical adsorption desorption instrument. A small amount of the molded catalyst is weighed, treated at 300°C under vacuum for 3 hours, cooled to room temperature, and then purged with N2 at different pressures at liquid nitrogen temperature to obtain N2 physical adsorption desorption isotherms, which are analyzed, and the surface area, pore size distribution and pore volume of the catalyst molded body are respectively obtained using the BET fitting formula, BJH and t-plot methods.

[0038] Example 1

[0039] (1) Prepare 1 mol / L chromium nitrate and 1 mol / L copper nitrate solution as liquid A, prepare 8% ammonia water as liquid B, add liquid A and liquid B into the reactor in parallel, react at 40°C for 1 hour, and maintain the pH value at 8.0±0.1 during the reaction. The obtained slurry is aged at room temperature for 6 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is placed in an air atmosphere and calcined at 500°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3 and CuCr2O4, and the mass fraction of Cr in the catalyst powder is 40wt%.

[0040] (2) Prepare a 5 wt% carboxymethyl cellulose solution, wherein the carboxymethyl cellulose has a viscosity of 800 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 100 g of the solution and add it to 200 g of catalyst powder, then add 50 g of deionized water and mix well. In the prepared mixed material, the amount of additive I added is 2.5 wt% of the catalyst powder, and the water content of the mixed material is 72.5 wt%.

[0041] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 4wt%. The crushed mixed material was obtained by ball milling at a speed of 100rpm for 15min, and then sieved. Weigh 20g, 70g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 3g of flake graphite (particle size of 400 mesh) and 2g of starch were added thereto, and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0042] (4) The tablets were calcined at 500°C for 4 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0043] Example 2

[0044] (1) Prepare 1 mol / L chromic anhydride solution as liquid A and 1 mol / L ammonium carbonate as liquid B, add liquid A and liquid B into the reactor in parallel, react at 50°C for 2 hours, and maintain the pH value at 7.0±0.1 during the reaction. The obtained slurry is aged at 50°C for 2 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 500°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3.

[0045] (2) Prepare a 4 wt% carboxymethyl cellulose solution, wherein the carboxymethyl cellulose has a viscosity of 600 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 150 g of the solution and add it to 200 g of catalyst powder and mix evenly. In the prepared mixed material, the amount of additive I added is 3 wt% of the catalyst powder, and the water content of the mixed material is 72 wt%.

[0046] (3) The mixed material obtained in step (2) is dried at 100°C for 4 hours, and the moisture content of the dried material is measured to be 2wt%. The crushed mixed material is obtained by a swing granulator and then sieved. Weigh 10g, 80g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials are mixed evenly, 1g of flake graphite (particle size is 1600 mesh) and 3g of polyvinyl alcohol are added thereto and mixed evenly again. The mixed materials are poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0047] (4) The tablets were calcined at 500°C for 4 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0048] Example 3

[0049] (1) Prepare a mixed solution of 1 mol / L chromium nitrate and 1 mol / L ferric nitrate as liquid A, prepare 1 mol / L ammonium bicarbonate as liquid B, add liquid A and liquid B into the reactor in parallel, react at 50°C for 1 hour, and maintain the pH value at 6.5±0.1 during the reaction. The obtained slurry is aged at 50°C for 4 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 450°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3.

[0050] (2) Prepare a 10 wt% carboxymethyl cellulose solution, wherein the carboxymethyl cellulose has a viscosity of 1000 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 50 g of the solution and 100 g of water and add them to 200 g of catalyst powder and mix them evenly. In the prepared mixed material, the amount of additive I added is 2.5 wt% of the catalyst powder, and the water content of the mixed material is 72.5 wt%.

[0051] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 2wt%. The crushed mixed material was obtained by a swing granulator and then sieved. Weigh 20g, 70g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 0.5g of flake graphite and 3g of carboxymethyl cellulose were added thereto and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0052] (4) The tablets were calcined at 450°C for 3 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0053] Example 4

[0054] (1) Prepare 1 mol / L chromic anhydride and 1 mol / L ferric nitrate as liquid A, prepare 2 mol / L sodium carbonate as liquid B, add liquid A and liquid B into the reactor in parallel, react at 30°C for 1.5 hours, and maintain the pH value at 7.0±0.1 during the reaction. The obtained slurry is aged at 30°C for 6 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 400°C for 3 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3.

[0055] (2) Prepare a 5 wt% hydroxypropyl methylcellulose solution, wherein the viscosity of the hydroxypropyl methylcellulose is 6000 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 100 g of the solution and 5 g of water and add them to 200 g of catalyst powder and mix them evenly. In the prepared mixed material, the amount of additive I added is 2.5 wt% of the catalyst powder, and the water content of the mixed material is 50 wt%.

[0056] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 2wt%. The crushed mixed material was obtained by a swing granulator and then sieved. Weigh 15g, 80g, and 5g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 3g of flake graphite (particle size of 800 mesh) and 2g of stearic acid were added thereto, and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0057] (4) The tablets were calcined at 425°C for 4 h at a heating rate of 5°C / min to obtain a molded catalyst.

[0058] Example 5

[0059] (1) Prepare 1 mol / L chromic anhydride and 1 mol / L copper nitrate as liquid A, prepare 10% ammonia water as liquid B, add liquid A and liquid B into the reactor in parallel, react at 50°C for 1 hour, and maintain the pH value at 7.0±0.1 during the reaction. The obtained slurry is aged at 50°C for 4 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 450°C for 3 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3 and CuCr2O4.

[0060] (2) Prepare a 10 wt% hydroxypropyl methylcellulose solution, wherein the viscosity of the hydroxypropyl methylcellulose is 2000 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 60 g of the solution and 66 g of water and add them to 200 g of catalyst powder and mix them evenly. In the prepared mixed material, the amount of hydroxypropyl methylcellulose (auxiliary agent I) added is 3 wt% of the catalyst powder, and the water content of the mixed material is 60 wt%.

[0061] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 2.5wt%. The crushed mixed material was obtained by a swing granulator and then sieved. Weigh 15g, 75g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 1g of flake graphite (particle size of 2000 mesh) and 4g of sesbania powder were added thereto and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0062] (4) The tablets were calcined at 450°C for 3 h at a heating rate of 1°C / min to obtain a molded catalyst.

[0063] Comparative Example 1

[0064] (1) Prepare 1 mol / L chromium nitrate and 1 mol / L copper nitrate solution as liquid A, prepare 8% ammonia water as liquid B, add liquid A and liquid B into the reactor in parallel, react at 40°C for 1 hour, and maintain the pH value at 8.0±0.1 during the reaction. The obtained slurry is aged at room temperature for 6 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is placed in an air atmosphere and calcined at 500°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3 and CuCr2O4, and the mass fraction of Cr in the catalyst powder is 40wt%.

[0065] (2) Weigh 100 g of catalyst powder, add 3 g of flake graphite (particle size 400 mesh) and 2 g of starch, and mix well. Pour the mixed material into the hopper of a tablet press and press into 3 mm × 3 mm tablets to obtain tablets.

[0066] (3) The tablets were calcined at 500°C for 4 h with a heating rate of 2°C / min.

[0067] In this comparative example, the catalyst powder was not pretreated, and flake graphite and starch were directly mixed for tableting, and other conditions were the same as those in Example 1. During the tableting process, the adjustable properties of the machine were poor, and under the premise of achieving the strength performance index, the height of the molded body was difficult to decrease, and the height of the molded body was too high.

[0068] Comparative Example 2

[0069] (1) Prepare 1 mol / L chromium nitrate and 1 mol / L copper nitrate solution as liquid A, prepare 8% ammonia water as liquid B, add liquid A and liquid B into the reactor in parallel, react at 40°C for 1 hour, and maintain the pH value at 8.0±0.1 during the reaction. The obtained slurry is aged at room temperature for 6 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is placed in an air atmosphere and calcined at 500°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3 and CuCr2O4, and the mass fraction of Cr in the catalyst powder is 40wt%.

[0070] (2) Prepare a 5 wt% carboxymethyl cellulose solution, wherein the carboxymethyl cellulose has a viscosity of 800 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 100 g of the solution and add it to 200 g of catalyst powder, then add 50 g of deionized water and mix well. In the prepared mixed material, the amount of additive I added is 2.5 wt% of the catalyst powder, and the water content of the mixed material is 72.5 wt%.

[0071] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 4wt%. The mixed material was crushed by ball milling at 100rpm for 15min. 100g of the crushed material was weighed, and 3g of flake graphite (particle size of 400 mesh) and 2g of starch were added thereto, and the mixture was mixed again. The mixed material was poured into the hopper of a tablet press, and tablets of 3mm×3mm were obtained.

[0072] (4) The tablets were calcined at 500°C for 4 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0073] In the comparative example, serious powder leakage and significant local cracking of the molded body were found during the tableting process. In addition, due to the uneven distribution of particle size, the filling efficiency was low and the packing density of the molded body was low. At the same time, since the particles could not be closely packed together, the contact area between the particles was small, resulting in calcination inertia, so that some large pores formed during the molding process still existed after calcination, thereby reducing the strength of the catalyst.

[0074] Comparative Example 3

[0075] (1) Prepare 1 mol / L chromium nitrate and 1 mol / L copper nitrate solution as liquid A, prepare 8% ammonia water as liquid B, add liquid A and liquid B into the reactor in parallel, react at 40°C for 1 hour, and maintain the pH value at 8.0±0.1 during the reaction. The obtained slurry is aged at room temperature for 6 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is placed in an air atmosphere and calcined at 500°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3 and CuCr2O4, and the mass fraction of Cr in the catalyst powder is 40wt%.

[0076] (2) Prepare a 5 wt% carboxymethyl cellulose solution, wherein the carboxymethyl cellulose has a viscosity of 800 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then add 10 g of the solution to 200 g of catalyst powder, and then add 135.5 g of water and mix well. At this time, the amount of additive I added is 0.25 wt%, and the water content of the mixed material is 72.5 wt%.

[0077] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 4wt%. The crushed mixed material was obtained by ball milling at a speed of 100rpm for 15min, and then sieved. Weigh 20g, 70g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 3g of flake graphite (particle size of 400 mesh) and 2g of starch were added thereto, and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0078] (4) The tablets were calcined at 500°C for 4 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0079] In this comparative example, due to the addition of less additive 1, the catalyst powder is difficult to agglomerate, and a pre-densified material with a certain strength cannot be obtained. The mixed material obtained in step (2) is re-powdered during the ball milling process, so that a material with a certain particle size distribution cannot be obtained. In addition, the amount of additive 1 added is small, resulting in limited optimization of the compression properties of the powder. Under the premise of achieving the catalyst strength index, the height of the catalyst is relatively high.

[0080] Comparative Example 4

[0081] (1) Prepare a mixed solution of 1 mol / L chromium nitrate and 1 mol / L ferric nitrate as liquid A, prepare 1 mol / L ammonium bicarbonate as liquid B, add liquid A and liquid B into the reactor in parallel, react at 50°C for 1 hour, and maintain the pH value at 6.5±0.1 during the reaction. The obtained slurry is aged at 50°C for 4 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 450°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3.

[0082] (2) Prepare a 10 wt% carboxymethyl cellulose solution, wherein the carboxymethyl cellulose has a viscosity of 1000 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 120 g of the solution and 37 g of water and add them to 200 g of catalyst powder and mix them evenly. In the prepared mixed material, the amount of additive I added is 6 wt% of the catalyst powder, and the water content of the mixed material is 72.5 wt%.

[0083] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 2wt%. The crushed mixed material was obtained by a swing granulator and then sieved. Weigh 20g, 70g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 0.5g of flake graphite and 3g of carboxymethyl cellulose were added thereto and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0084] (4) The tablets were calcined at 450°C for 3 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0085] In this comparative example, due to the addition of more additive 1, the strength of the pre-densified material is too high, making the subsequent crushing process difficult. Due to the excessive addition of additive 1, in step (4), the gas generated by pyrolysis escapes from the inside of the molded body, causing impact on the molded body, resulting in an increase in the scrap rate, a significant decrease in the strength of the molded body, and the finished product cannot meet the catalyst application index.

[0086] Comparative Example 5

[0087] (1) Prepare 1 mol / L chromic anhydride solution as liquid A and 1 mol / L ammonium carbonate as liquid B, add liquid A and liquid B into the reactor in parallel, react at 50°C for 2 hours, and maintain the pH value at 7.0±0.1 during the reaction. The obtained slurry is aged at 50°C for 2 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 500°C for 4 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3.

[0088] (2) Weigh 100 g of catalyst powder, add 1 g of flake graphite (1600 mesh) and 3 g of polyvinyl alcohol, and mix again. Pour the mixed material into the hopper of a tablet press and press into 3 mm × 3 mm tablets to obtain tablets.

[0089] (3) The tablets were calcined at 500°C for 4 h at a heating rate of 2°C / min to obtain a molded catalyst.

[0090] In this comparative example, the powder was not pretreated, and flake graphite and polyvinyl alcohol were directly mixed for tableting, and other conditions were the same as those in Example 2. During the tableting process, the adjustable properties of the machine were poor, and under the premise of achieving the strength performance index, the height of the molded body was difficult to decrease, and the height of the molded body was too high.

[0091] Comparative Example 6

[0092] (1) Prepare 1 mol / L chromic anhydride and 1 mol / L copper nitrate as liquid A, prepare 10% ammonia water as liquid B, add liquid A and liquid B into the reactor in parallel, react at 50°C for 1 hour, and maintain the pH value at 7.0±0.1 during the reaction. The obtained slurry is aged at 50°C for 4 hours and then taken out and filtered. After washing with deionized water until the effluent is neutral, the filter cake is dried at 100°C. After cooling to room temperature, the precursor is calcined at 450°C for 3 hours to obtain a catalyst powder. Cr exists in the form of Cr2O3 and CuCr2O4.

[0093] (2) Prepare a 10 wt% hydroxypropyl methylcellulose solution, wherein the viscosity of the hydroxypropyl methylcellulose is 2000 mPa.s. Stir and mix at room temperature until it becomes viscous and free of white agglomerates, then take 90 g of the solution and 39 g of water and add them to 200 g of catalyst powder and mix them evenly, wherein the amount of hydroxypropyl methylcellulose (auxiliary agent I) added is 4.5 wt% of the catalyst powder, and the water content of the mixed material is 60 wt%.

[0094] (3) The mixed material obtained in step (2) was dried at 100°C for 4 hours, and the moisture content of the dried material was measured to be 2.5wt%. The crushed mixed material was obtained by a swing granulator and then sieved. Weigh 15g, 75g, and 10g of powders ≥40 mesh and <80 mesh, 80-120 mesh, and greater than 120 mesh, respectively. After the three materials were mixed evenly, 1g of flake graphite (particle size of 2000 mesh) and 4g of sesbania powder were added thereto and mixed evenly again. The mixed materials were poured into the hopper of a tablet press and compressed into 3mm×3mm tablets to obtain tablets.

[0095] (4) The tablets were calcined at 450°C for 3 h at a heating rate of 1°C / min to obtain a molded catalyst.

[0096] In this comparative example, due to the addition of more additive 1, the strength of the pre-densified material is too high, making the subsequent crushing process difficult. Due to the excessive addition of additive 1, in step (4), the gas generated by pyrolysis escapes from the inside of the molded body, causing impact on the molded body, resulting in an increase in the scrap rate, a significant decrease in the strength of the molded body, and the finished product cannot meet the catalyst application index.

[0097] Table 1 Parameters of the catalysts in the examples and comparative examples

[0098]

[0099] The specific embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical features of the present invention can be combined in any other suitable manner, and these simple variations and combinations should also be regarded as the scope disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A tabletting method for a Cr-based catalyst, characterized in that: include: (1) Cr-based catalyst powder is prepared by co-precipitation method; The Cr-based catalyst powder is a calcined powder; (2) mixing the Cr-based catalyst powder obtained in step (1), the aqueous solution of the additive I and the optionally added water to obtain a mixed material; (3) drying, crushing, and screening the mixed material obtained in step (2), and then mixing with auxiliary agent II and auxiliary agent III, and tableting to obtain tablets; (4) calcining the tablets prepared in step (3) to obtain the molded catalyst.

2. The method according to claim 1, characterized in that: In the Cr-based catalyst powder obtained in step (1), the mass fraction of Cr is 40wt% to 100wt%.

3. The method according to claim 1, characterized in that: The calcination conditions in step (1) are as follows: the calcination temperature is 350-650° C., the calcination time is 3-6 hours, and the calcination atmosphere is an oxygen-containing atmosphere.

4. The method according to claim 1, characterized in that: In step (2), the auxiliary agent I is cellulose; preferably at least one of carboxymethyl cellulose and hydroxypropyl methyl cellulose; more preferably, the viscosity of the carboxymethyl cellulose is 200mpa.s to 1000mpa.s, and the viscosity of the hydroxypropyl methyl cellulose is 2000mpa.s to 6500mpa.s; And / or, in the aqueous solution of the auxiliary agent I, the mass content of cellulose is 1 wt% to 10 wt%.

5. The method according to claim 1 or 4, characterized in that: In step (2), the amount of additive I added is 1wt% to 3wt% of the Cr-based catalyst powder.

6. The method according to claim 1, characterized in that: In step (2), the amount of water added is sufficient to ensure that the final water content of the prepared mixed material is 50wt% to 80wt%.

7. The method according to claim 1, characterized in that: In step (3), the drying temperature is 80° C. to 120° C., and the moisture content of the material after drying is 2wt% to 10wt%.

8. The method according to claim 1, characterized in that: In step (3), the screening is divided into three parts according to ≥40 mesh and <80 mesh, 80-120 mesh and >120 mesh, and the three parts of materials are mixed in a mass ratio of 10-20:60-80:5-10.

9. The method according to claim 1, characterized in that: In step (3), the auxiliary agent II is graphite, and the graphite is at least one of natural graphite and artificial graphite; the particle size of the auxiliary agent II is above 200 mesh, preferably 400 mesh to 2000 mesh.

10. The method according to claim 1 or 9, characterized in that: In step (3), the amount of additive II added is 0.5wt% to 3wt% of the Cr-based catalyst powder.

11. The method according to claim 1, characterized in that: In step (3), the auxiliary agent III is at least one of starch, epoxy resin, carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol, sesbania powder, and stearic acid.

12. The method according to claim 1 or 11, characterized in that: In step (3), the amount of additive III added is 1wt% to 5wt% of the Cr-based catalyst powder.

13. The method according to claim 1, characterized in that: In step (4), the calcination temperature is 300°C to 600°C, the heating rate is 0.5°C / min to 5°C / min, and the calcination time is 2h to 8h.

14. A Cr-based catalyst prepared according to the method according to any one of claims 1 to 13.

15. The Cr-based catalyst according to claim 14, characterized in that: The radial strength of the Cr-based catalyst is 50 N / grain or more, preferably 60 N / grain to 120 N / grain, and the specific surface area is 20 m 2 / g~50m 2 / g, average pore diameter is 15nm~35nm, pore volume is 0.08cm 3 / g~0.15cm 3 / g.

Citation Information

Patent Citations

  • Preparation method of copper-chromium catalyst

    CN103769115A

  • Fluorination catalyst and preparation method thereof

    CN107670659A

  • Method for improving forming strength of catalyst, catalyst and application thereof

    CN109569742A

  • Aldehyde hydrogenation catalyst and preparation method thereof

    CN113042060A

  • Molding method and application of catalyst

    CN114471575A

Cited By

  • Tabletting method and mold for improving forming rate of catalyst

    CN121756650A